Pengaruh Abu Bonggol Jagung sebagai Filler pada Campuran Aspal AC-WC terhadap Karakteristik Marshall - Ida Farida; Wiguna Rahmana (Institut Teknologi Garut, 2026)
The population growth in Indonesia has increased significantly. The increase in population is directly proportional to the increase in vehicle volume. There is a need for adequate transportation infrastructure, especially in the quality of the pavement layer. Corncob is an agricultural waste that has the potential to be used in road construction. The ash from burning corncobs contains an element similar to cement, namely silica. The silica content in corncob ash reaches 66.83%. This research aims to analyze the effect of corncob ash as filler in AC-WC asphalt mixture on Marshall characteristics. Primary data were obtained from laboratory tests using variations of corncob ash content (1.5%, 2.5%, 3.5%). The results showed that the optimum level of corncob ash increased the stability and yield of the asphalt mixture. Recommendations include the utilization of corncob ash as an environmentally friendly alternative to improve the quality of pavement layers.